ESTIMATION CARBON STOCK ON MANGROVE VEGETATION AT MANGROVE AREA OF UJUNG PIRING JEPARA DISTRICT - Dimas Panji Budi Prasetyo; Ria Azizah Tri Nuraini; Endang Supriyantini (International Journal of Marine and Aquatic Resource Conservation and Co-existence, 2017)
ABSTRACTMangrove forrest is an coastal ecosystem which has so many advantages and usages. Mangrove forrest has ecological functions as carbon sink.  This function becomes very important because of the increased greenhouse gas (GHG) emissions in the atmosphere causing climate change. Climate change raises the temperature on the surface of the earth, thus threatening the existence of humans and other living things. The purpose of this research was to determine the amount of biomass, carbon reserve, CO2 absorption and soil organic carbon in mangrove vegetation Ujung Piring, Jepara.The method used in this research was descriptive and location determined by purposive sampling, which is divided into three locations, in each location used 2-3 x sampling. The data were collected using a 10 x 10 m plot. Determination of stored biomass in stands using non-destructive sampling by measuring stem diameter (Dbh) and allometric equation on each mangrove species. Carbon stock was determined using the results of biomass determination, whereas CO2 absorption was determined using carbon stock. Soil organic carbon is determined using the results of organic matter measurement.The result showed that 6 mangroves species were found in the research plots: Rhizophora apiculata, Rhizophora mucronata, Ceriops tagal, Lumnitzera racemosa, Sonneratia alba, and Sonneratia caseolaris. The largest carbon stock value is in Location I with the dominance of R.apiculata. The carbon stock of mangrove vegetation has a linear relationship with soil organic carbon. Ujung Piring has amount of biomass 16,69 ton/ha, carbon stock 7,85 ton/ha,  CO2 absorption 28,76 ton/ha and soil organic carbon 1706 ton/ha. Key words: Biomass, Carbon Stock, CO2 Absorption, Mangrove forrest, Soil Organic Carbon